Management of bimaxillary protrusion with missing molar using T-loop and couple force - Ida Bagus Narmada; Shali Wikynikta Purnomo; Putri Intan Sitasari; Nabilla Vidyazti Rishandari Prasetyo; Aldila Rahma (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Management of bimaxillary protrusion can be challenging and should be used with maximum anchorage to prevent loss of anchorage and improve the facial profile. In addition, a patient with a missing molar is often found in a dental clinic. Space closure can cause tipping movement rather than bodily, so couple force should be used. Purpose: This case report aims to manage the bimaxillary protrusion with a missing molar using a T-loop and a transpalatal arch (TPA) as maximum anchorage for correction of the facial profile and couple force to create bodily movement for the space closure of a missing first molar. Case: A 21-year-old female patient complained about her protruding teeth. An intraoral examination indicated Angle’s Class I malocclusion on the left molar relation, with the lower-right first molar missing, mild crowding maxilla and mandible, 6 mm of overjet and 5 mm of overbite, and midline shift at the maxilla and mandible. Case Management: The treatment plan was the extraction of teeth 14, 24, 34; alignment with pre-adjusted McLaughlin Bennett Trevisi (MBT) 0.022; retraction of the anterior segment with a T-loop, TPA, and close spacing of the missing first molar with couple force on the buccal and lingual side and tip back. Retention was done with removable retainers. At the end of the treatment, normal incisive inclination and closed space of the missing first molar were achieved, along with an improvement of the facial profile. Conclusion: Bimaxillary protrusion can be successfully treated by means of extraction of the premolar(s), space closure for correction of the profile with T-loop and TPA, and closing the space of the missing molar with couple force on the buccal and lingual sides and tip back.